The effect of joint translation constraint on within-participant variability of kinematics and kinetics during running in cerebral palsy. (March 2019) - Chappell, A.; Liew, B.; Murphy, A.T.; Gibson, N.; Allison, G.T.; Williams, G.; Morris, S.L.
Abstract: Background: Biomechanical data in cerebral palsy are inherently variable but no optimal model of translational joint constraint has been identified. The primary aim of this study was to determine which model of translational joint constraint resulted in the lowest within-participant variability of lower limb joint angles and moments. The secondary aim was to determine which model best distinguished known functional groups in Cerebral Palsy. Methods: Three models (three degrees of freedom, six degrees of freedom and six degrees of freedom with specified joint translation constraint) were applied to data from running trials of 40 children with cerebral palsy. Findings: Joint angle standard deviations were largest using the six degrees of freedom model and smallest using the constrained six degrees of freedom model ( p  < 0.050). For all joints in all planes of motion, joint moment standard deviations were largest using the six degrees of freedom model and smallest using the constrained six degrees of freedom model; standard deviations using the constrained model were smaller than the three degrees of freedom model by 10–30% of moment magnitude (0.01–0.03 Nm/kg; p  < 0.001). The six degrees of freedom models distinguished functional subgroups with larger effect size than the three degrees of freedom model only for hip power generation in swing. Interpretation: A model with specified joint constraint minimized within-participant variability during running and was useful for detecting differences in functional capacity in cerebral palsy. Highlights: A 6DoF biomechanical model with customised joint constraints is described. Customised joint translation constraints decrease extrinsic variability. This results in a larger effect size for hip power generation in swing.